KETIDAKPASTIAN DALAM PEMODELAN PERUBAHAN IKLIM - Ahmad Bayhaqi (Pusat Penelitian Oseanografi LIPI, 2019)
THE UNCERTAINTIES IN CLIMATE CHANGE MODELING. Climate in the Earth has changed over the periods and will be estimated to give the a significant impact for environment in the future. Climate prediction using a simulation model, as a tool to predict the future climate and it requires the high quantitative skills and technology, has showed the significant improvement. However, the climate model depends on the input variable and the result may be inaccurate because its biases and uncertainties. Information of the uncertainties in the climate model can determine the modification in climate change mitigation and show the way how to adapt with the inevitable changes.